STUDI KELAYAKAN APARTEMEN UNTUK GENERASI MILENIAL DI AREA STASIUN LRT GUNUNG PUTRI KABUPATEN BOGOR - Kent Demas Kynan; Priyendiswara Agustina Bela (Jurusan Arsitektur dan Perencanaan, 2021)
Feasibility Study is a study of an investment project to determine whether the project can be said to be feasible and implemented successfully. The Feasibility Study of a 1.6 hectare land in the planned area of the Gunung Putri LRT Station, Bogor Regency, has several unique feasibility study criteria. Its characteristics can be seen from the defined segmentation, such as Millennial Housing and the condition of environment has the potential for pollutants due to Toll Roads and Cement Factories. In this feasibility study, there are three main feasibility studies and one additional feasibility study were carried out. The feasibility is physical & legal feasibility, environmental health feasibility through ADKL analysis (Environmental Health Impact Analysis), market feasibility and investment feasibility. This Feasibility Study produces feasibility in all aspects with recommended requirements in the form of environmental mitigation with tamarind trees, application of the concept of millennial housing, choosing the right sales and construction time to see the conditions of the COVID-19 pandemic and choosing an alternative programming unit in investing. The results of this feasibility study are said to be physically and legally feasible, market and investment by considering the concept of Open Spaces, Green Concept, Integrity with Leisure and Business and Affordable Housing by selling units in the range of Rp. 16,850,000 / m2 plus the implementation of a Green Site. Selection of the 3rd Alternative with sales pursuit for a take up rate of at least 78% as the best alternative with the largest return. Keywords: Apartment; Feasibility Study; Green Site; Investment; Millennial Generations AbstrakStudi Kelayakan adalah suatu kajian mengenai proyek investasi untuk dapat menentukan apakah proyek tersebut dapat dikatakan layak dan dilaksanakan dengan berhasil. Studi Kelayakan lahan seluas 1,6 Ha di area rencana Stasiun LRT Gunung Putri Kabupaten Bogor memiliki beberapa kriteria studi kelayakan yang unik. Karakteristiknya dapat dilihat dari segmentasi yang ditetapkan yaitu Generasi Milenial dan lingkungan berpotensi polutan oleh sebab Jalan Tol dan Pabrik Semen. Pada studi kelayakan ini dilaksanakan tiga kelayakan utama dan satu kelayakan tambahan. Kelayakan tersebut adalah kelayakan fisik & hukum, kelayakan kesehatan lingkungan lewat analisis ADKL (Analisis Dampak Kesehatan Lingkungan), kelayakan pasar dan kelayakan secara investasi. Studi Kelayakan ini menghasilkan kelayakan diseluruh aspek dengan syarat rekomendasi berupa mitigasi lingkungan dengan pohon trembesi, penerapan konsep hunian milenial, pemilihan waktu penjualan dan waktu konstruksi yang tepat melihat kondisi pandemi COVID-19 serta pemilihan alternatif programming unit dalam berinvestasi. Hasil dari studi kelayakan ini dikatakan layak secara fisik dan legal, pasar dan investasi dengan mempertimbangkan konsep Open Spaces, Green Concept, Integrity with Leisure and Business dan Affordable Housing dengan menjual unit di kisaran Rp. 16.850.000/m2 ditambah dengan penerapan Green Site. Pemilihan Alternatif ke-3 dengan pengejaran penjualan untuk take up rate minimal 78% sebagai alternatif terbaik dengan pengembalian terbesar.